Hydrogel Based on Crosslinked Methylcellulose Prepared by Electron Beam Irradiation for Wound Dressing Application - Ambyah Suliwarno (Universitas Gadjah Mada, 2014)
The aim of this research is to explore the possibility of methylcellulose polymer to be used as wound dressing material prepared using electron beam technique. The methylcellulose paste solution with various of molecular weight (SM-4, SM-100, SM-400, SM-4000 and SM-8000) at different concentration (15-30% w/v) were irradiated by using electron beam on the dose range of 10 kGy up to 40 kGy. Gel fraction and swelling ratio of hydrogels were determined gravimetrically. Tensile strength and elasticity of hydrogels were measured using a universal testing machine. It was found that with the increasing of irradiation dose from 10 up to 40 kGy, gel fraction and tensile strength were increased for all of hydrogels with various of molecular weight. On contrary, the swelling ratio of hydrogels decreased with increasing of irradiation dose. The optimum hydrogels elasticity were obtained from methylcellulose solution with the concentration range of 15-20% with irradiation dose of 20 kGy and showed excellent performance. The hydrogels based on methylcellulose prepared by electron beam irradiation can be considered for wound dressing material.